ADMINSTRATION AND MANAGEMENT OF PROFESSIONAL FOOTBALL CLUB IN THE UPPER SOUTHERN PROVINCIAL ZONE - Pairat, Kanokwan; Choeychom, Kongkiat; Sriwisut, Panu (Academic Journal of Thailand National Sports University, 2023)
The purpose of this research was to study the adminstration and management of professional football club in the upper southern provinces zone. The adminstration and Management as mentioned consisted of 5 aspcet such as personnel, finance and budget, location, materials and facilities, and operations. The population of this research were managers, coaches and athletes of five football clubs in the upper southern provincial zone, such as Nakhon Si United Football Club, Surat Thani City Club, Surat Thani FC Club, Krabi Football Club FC and Patong City Club, totaling 185 people. The sample group of this research was by quota randomization, totaling 130 people. The research tool were questionnaires, consisted of Checklist, ratting scale, and open - ended questions. In this study, the IOC index of content validity was .70. and reliability of the question was 0.97. The statistics for data analysis were frequency, percentage, mean, standard deviation One-way analysis of and multiple comparison (Tukey’s test). The results were as follows: The highest mean is operations followed by personnel, finance and budget, location, materials and facilities respectively. From the results of this research it is able to apply the various aspects that are involved in management to be a guideline for managing football clubs more effectively.